2016
DOI: 10.1007/s10509-015-2639-2
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin–Helmholtz instability in an active region jet observed with Hinode

Abstract: Over past ten years a variety of jet-like phenomena were detected in the solar atmosphere, including plasma ejections over a range of coronal temperatures being observed as extreme ultraviolet (EUV) and X-ray jets. We study the possibility for the development of Kelvin-Helmholtz (KH) instability of transverse magnetohydrodynamic (MHD) waves traveling along an EUV jet situated on the west side of NOAA AR 10938 and observed by three instruments on board Hinode on 2007 January 15/16 (Chifor et al., Astron. Astrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…This result is readily applicable to standing waves, as Ruderman (2018) showed that the growth rate of a standing wave is equal to the growth rate of the propagating wave with negative energy minus the damping rate of the propagating wave with positive energy. Zhelyazkov et al (2016) carried out case studies on observed coronal jets and stated that the onset of KHI regarding kink waves depends on whether the plasma jet is incompressible or compressible, as the incompressibility elevates the KHI threshold speed. The magnetic twist of the jet decreases the KHI threshold speed.…”
Section: Negative Energy Wave Effects On Kink Oscillationsmentioning
confidence: 99%
“…This result is readily applicable to standing waves, as Ruderman (2018) showed that the growth rate of a standing wave is equal to the growth rate of the propagating wave with negative energy minus the damping rate of the propagating wave with positive energy. Zhelyazkov et al (2016) carried out case studies on observed coronal jets and stated that the onset of KHI regarding kink waves depends on whether the plasma jet is incompressible or compressible, as the incompressibility elevates the KHI threshold speed. The magnetic twist of the jet decreases the KHI threshold speed.…”
Section: Negative Energy Wave Effects On Kink Oscillationsmentioning
confidence: 99%
“…It is worth pointing out, however, that for a twisted magnetic field the magnitude of the axial magnetic field component B iz , which is used for computing both ε 1 and v Ai , is less than B i itself. This implies that the reference Alfvén speed v Ai must be corrected along with the magnetic fields ratio b, notably b should be replaced by b twist = b 1 + ε 2 1 and, accordingly, v Ai → v Ai / 1 + ε 2 1 (see Zhelyazkov et al (2016)). The diminished value of v Ai requires a correction of the Alfvén Mach number, too, namely M A should be replaced by M A 1 + ε 2 1 .…”
Section: Dispersion Curves and Growth Rates Of The Unstable M = 2 Mhdmentioning
confidence: 99%
“…There is an unexpected peculiarity-the threshold Alfvén Mach number for instability arising turns out to be lower than that in untwisted flux tube, notably equal to 2.30839, which yields a critical flow speed of ≈308 km s −1 -24 km s −1 less than the average jet speed. An (Zhelyazkov et al, 2016).…”
Section: Kink Mode Propagation Characteristics At a Density Contrast mentioning
confidence: 99%